2019
DOI: 10.30723/ijp.v17i43.483
|View full text |Cite
|
Sign up to set email alerts
|

Estimating sugar concentration in human blood serum using Surface Plasmon Resonance (SPR) –based optical fiber sensor

Abstract: Surface Plasmon Resonance (SPR)-based plastic optical fiber sensor for estimating the concentration and refractive index of sugar in human blood serum. The sensor is fabricated by a small part (10mm) of optical fiber in the middle is embedded in a resin block and then the polishing process is done, after that it is deposited with about (40nm) thickness of gold metal. The blood serum is placed on gold coated core of an Optical grade plastic optical fiber of 980 µm core diameter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Raham et al demonstrated a plastic optical fiber sensor based on Surface Plasmon Resonance (SPR) for estimating the concentration and refractive index of sugar in human blood serum. The refractive index increases as the resonance wavelength increases, as evidenced by the fact that at resonance wavelength (613 nm), the refractive index was (1.3628), which was increased by increasing the resonance wavelength until it reached its highest value of (1.387) at resonance wavelength (734 nm) 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Raham et al demonstrated a plastic optical fiber sensor based on Surface Plasmon Resonance (SPR) for estimating the concentration and refractive index of sugar in human blood serum. The refractive index increases as the resonance wavelength increases, as evidenced by the fact that at resonance wavelength (613 nm), the refractive index was (1.3628), which was increased by increasing the resonance wavelength until it reached its highest value of (1.387) at resonance wavelength (734 nm) 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Jassam suggested a chemical sensor using a plastic optical fiber, with a sensitivity of 3.3030m/RIU [15]. Rahim created an optical fiber biomedical sensor with a sensitivity of 7.5m/RIU employing surface plasmon resonance [16]. Ali and Al-Bassam designed and implemented a no-core optical fiber with a sensitivity of 11.11m/RIU for monitoring contaminated water [17].…”
Section: Introductionmentioning
confidence: 99%
“…Surface Plasmon Resonance (SPR) is defined as an optical phenomenon that occurs when p-polarized light excites a charge density oscillation at the metal-dielectric interface by achieving the phase-matching state between the p-polarized light and SP [5][6][7][8][9]. Combining the advantages of PCF technology with plasmonic science, PCF-SPR sensors have been developed for a wide range of potential applications such as water testing [10], food safety, solution concentration measurement [11], environmental monitoring, biochemistry research [12], gas detection, medical diagnostics, and so on [13].…”
Section: Introductionmentioning
confidence: 99%